Exploitation and Class Formation in the Inca State - Patterson, Thomas C. (Culture, 1985)
Inca society was characterized by conditions of expanded exploitation which were produced by new contradictions that emerged as the composition of the dominant class changed. The expansionist policies of the Inca ruling class were an attempt to resolve problems resulting from an internal organization based on kinship. The collateral kin of the ruler were necessary for maintaining the dominant position of the Incas, but their claims to the throne made them unreliable allies. Rulers of the conquest state assured their loyalty by allowing them to extract surplus labor from the direct producers in the core areas of the empire. Consequently, the rulers themselves were forced to seek additional surplus by displacing their demands onto subjugated communities and polities. The new forms of exploitation that emerged initially emphasized control of local shrines or alliances with their spokesmen. Later, the politically dominant elements emphasized the creation of alliances with powerful shrines in newly conquered areas. Still later, land was appropriated not only for the direct use of Inca ruling class but also as gifts to be given to traditional leaders of ethnic groups or to other individuals who promoted the well-being of the Inca state and its dominant class. The new alliances created the conditions for the formation of social classes, that were not identical with earlier forms of social stratification — regardless of whether they were based on kinship or class.